tn=n(5n-9)

Simple and best practice solution for tn=n(5n-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for tn=n(5n-9) equation:


Simplifying
tn = n(5n + -9)

Reorder the terms:
nt = n(-9 + 5n)
nt = (-9 * n + 5n * n)
nt = (-9n + 5n2)

Solving
nt = -9n + 5n2

Solving for variable 'n'.

Reorder the terms:
9n + nt + -5n2 = -9n + 5n2 + 9n + -5n2

Reorder the terms:
9n + nt + -5n2 = -9n + 9n + 5n2 + -5n2

Combine like terms: -9n + 9n = 0
9n + nt + -5n2 = 0 + 5n2 + -5n2
9n + nt + -5n2 = 5n2 + -5n2

Combine like terms: 5n2 + -5n2 = 0
9n + nt + -5n2 = 0

Factor out the Greatest Common Factor (GCF), 'n'.
n(9 + t + -5n) = 0

Subproblem 1

Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0

Subproblem 2

Set the factor '(9 + t + -5n)' equal to zero and attempt to solve: Simplifying 9 + t + -5n = 0 Reorder the terms: 9 + -5n + t = 0 Solving 9 + -5n + t = 0 Move all terms containing n to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -5n + -9 + t = 0 + -9 Reorder the terms: 9 + -9 + -5n + t = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -5n + t = 0 + -9 -5n + t = 0 + -9 Combine like terms: 0 + -9 = -9 -5n + t = -9 Add '-1t' to each side of the equation. -5n + t + -1t = -9 + -1t Combine like terms: t + -1t = 0 -5n + 0 = -9 + -1t -5n = -9 + -1t Divide each side by '-5'. n = 1.8 + 0.2t Simplifying n = 1.8 + 0.2t

Solution

n = {0, 1.8 + 0.2t}

See similar equations:

| x(x+2)=158 | | 5x+9=3x+3 | | 9x^2-54x=-69 | | x-2*3=-6 | | x-2*0=-6 | | -16x^2+22x+100=80 | | -2(7x+1)=6(1-3x)+2 | | 9=y/x | | -(3y+2)-(-2y-4)=-3 | | 4B-7=15 | | 4AB-7A=15A | | 9=x/y | | 36x^2=3600 | | a+6/3=a/2 | | Y=-3/5x+7 | | 4y-9-5y+12=0 | | 3x+4x=-77 | | 2(2-x)=3(4-2x) | | 4+y=-5 | | x/4+1=x | | 15x+(x^2)=64 | | Cx-9x=5 | | .5x(2x-6)=-6 | | 5(x-4)=55 | | 3/10x+14.8=21.2 | | 6x+2x-8=5x-17 | | 1/2t-3.99=4.76 | | 3n-6=-21 | | 9x+29=6x+77 | | 5/6*x-1/5*x+4=7/10*x | | 2x^2+3x^2=144 | | 2a^2+36=18 |

Equations solver categories